2021
DOI: 10.1038/s12276-021-00670-3
|View full text |Cite
|
Sign up to set email alerts
|

MRTF-A-NF-κB/p65 axis-mediated PDL1 transcription and expression contributes to immune evasion of non-small-cell lung cancer via TGF-β

Abstract: PD-L1 is abnormally regulated in many cancers and is critical for immune escape. Fully understanding the regulation of PD-L1 expression is vital for improving the clinical efficacy of relevant anticancer agents. TGF-β plays an important role in the low reactivity of PD-1/PD-L1 antibody immunotherapy. However, it is not very clear whether and how TGF-β affects PD-L1 expression. In the present study, we show that TGF-β upregulates the expression of the transcriptional coactivator MRTF-A in non-small-cell lung ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 59 publications
(74 reference statements)
1
23
0
Order By: Relevance
“…In this axis, Myocardin-related transcription factor-A (MRTF-A) plays an immune suppressive function. Rho/ROCK signaling is involved in the noncanonical pathway to suppress TGF-β induced PD-L1 expression, contributing the translocation of MRTF-A to the nucleus [ 140 ].…”
Section: Rock and Cancer Immunotherapymentioning
confidence: 99%
“…In this axis, Myocardin-related transcription factor-A (MRTF-A) plays an immune suppressive function. Rho/ROCK signaling is involved in the noncanonical pathway to suppress TGF-β induced PD-L1 expression, contributing the translocation of MRTF-A to the nucleus [ 140 ].…”
Section: Rock and Cancer Immunotherapymentioning
confidence: 99%
“…In line with this, ROCK-mediated moesin phosphorylation regulated the PD-L1 stability by preventing its degradation in breast cancer cells [121]. In non-small cell lung cancer cells, TGF-β signaling upregulated the expression of MRTF (through a RhoA/ROCK non-canonical mechanism), which interacted with NF-κB/p65 to promote PD-L1 expression through transcription [122]. Whether these mechanisms occur in melanoma and their importance in the context of therapy resistance remain to be investigated.…”
Section: Perspective and Unanswered Questionsmentioning
confidence: 63%
“…MRTFA is strongly associated with cell viability of its correlation with cytoskeleton and actin ( 33 ). It has been identified as an EMT and metastasis regulator in NPC ( 34 ) and NSCLC ( 35 ). BTBD10 functions as an activator of AKT family members by inhibiting PPP2CA-mediated dephosphorylation, and a few studies have identified it as a prognostic risk factor in hepatocellular carcinoma ( 36 ) and glioma ( 37 ).…”
Section: Discussionmentioning
confidence: 99%